PENDAMPINGAN KOMPREHENSIF DALAM PENINGKATAN STRATEGI PEMASARAN DIGITAL DARI SOTO KUDUS KEDAI TAMAN CABANG MOJOKERTO - Achmad Sudiro; Mirza Dwinanda Ilmawan; Nindi Vaulia Puspita (Universitas Kadiri, 2025)
This community service activity aims to help UKM Kedai Soto Kudus Kedai Taman in Mojokerto in optimizing digital marketing. With the development of the Industrial Revolution 4.0, UKM needs to utilize social media to increase competitiveness. Mentoring is provided to managers and employees to be more effective in attracting customers through digital marketing strategies. The findings show that this UKM has not fully optimized digital tools to expand the market and increase the number of customers. Through training, participants understand how to create attractive promotional content, increase customer interaction, and optimize social media to increase sales conversions. As a result, after mentoring, UKM Kedai Soto Kudus Mojokerto succeeded in increasing the number of visitors and customers, supporting more stable and sustainable business growth in the digital era.